A STUDY OF EFL STUDENTS’ SPEAKING ANXIETY AT THE THIRD SEMESTER OF ENGLISH DEPARTMENT IN MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Rizkiani Aulia; Sitti Maryam Hamid; Sulkifli (FKIP Unismuh Makassar, 2023)
This study aimed to find out the factors of students speaking anxiety, the strategies used by students in overcoming anxiety in speaking English and the type of anxiety experienced by students when speaking English. This type of research is qualitative using descriptive method. The sampled in this research are students majoring in English education, semester 3 as many as 8 students. The instrument used in this research are observation and interview. The results of this research showed that there are 3 factors causing students' to feel anxiety, namely 3 students experienced communication apprehension, 2 students experienced test anxiety and 3 students who experienced fear of negative evaluation. The researcher also find out 3 types of anxiety that the students experienced in their speaking anxiety, the most dominant factor is situation specific anxiety, following by state anxiety and trait anxiety. The most dominant strategy used by students is positive thinking following by Preparation, Relaxation, Peer Seeking and Resignation.